Pengaruh Good Governance Terhadap Kinerja Pembangunan Perkotaan di Era Desentralisasi: (Studi Kasus Kota Surabaya 2019–2023) - Abdullah Wisnu Bayu (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
This study analyzes the influence of good governance on urban development performance in Surabaya during 2019-2023 using a quantitative descriptive approach and secondary data from BPS and local government. Good governance is measured by SPBE, while development performance is measured by HDI, economic growth, and poverty. The results show improved governance with a satisfactory SPBE index and positive development trends, including increasing HDI, economic recovery after 2020, and declining poverty after the pandemic. The findings indicate that good governance positively affects development performance by improving policy effectiveness, public services, and supporting economic and social recovery.